“The Comedy about David and Galiad” in Context of Western European Drama of the 16th–17th Centuries - М. V. Kaplun (Научный диалог, 2020)
The article is devoted to “The Comedy about David and Galiad,” staged at the court of Tsar Alexey Mikhailovich in 1676, in the context of Western European drama of the 16th–17th centuries. The material was a mounting sheet of the comedy of 1676, plays by French playwrights of the 16th century and texts of Russian court plays of the 1670s. The paper shows that the Russian comedy based on the story of David and Goliath fit well into the context of religious drama and could be correlated with the events of the Church reform in Russia. Special attention is paid to the comparative analysis of the plays of the French Calvinist playwrights Joachim de Coignac and Louis De Masur in order to identify common typological features of the Russian play and Western drama. The play ‘Temir-Aksakov Action” by Yu. M. Givner was brought to consideration in order to put forward a hypothesis about the possible author of the play of German origin. The author presents the latest development of the reconstruction of “The Comedy about David and Galiad,” based on a comparative approach and typological analysis of the literary and historical context of the 16th–17th centuries. The analysis shows the content aspect of the Russian play about David and Goliath, which incorporated the characteristic features of the Moscow court drama of the last third of the 17th century.